The Effect of Variations of Serum Examination Time Lapse on Electrolyte Levels of Potassium and Chloride: Pengaruh Variasi Selang Waktu Pemeriksaan Serum Terhadap Kadar Elektrolit Kalium dan Klorida - Asri, Nur Indah Nila; Aliviameita, Andika (Medicra (Journal of Medical Laboratory Science/Technology), 2022)
Electrolyte is a chemical substance that dissociates in the liquid into charged particles of positive and negative ions. In the laboratory, conditions are often found that make an examination not immediately carried out after sampling. The purpose of this study was to determine the effect of variations in serum examination time intervals on Potassium and Chloride electrolyte levels for 0, 4, 8 and 24 hours at room temperature (20-25℃). This study used a laboratory experimental method with a sample of 32 samples. This research was conducted at the Bhayangkara Hospital Pusdik Brimob Watukosek Laboratory. Examination of Potassium and Chloride electrolyte levels using the OPTI CCA-TS Analyzer. The results of the One Way Anova test for Potassium electrolyte levels obtained a significance p value of = 0,199 meaning that there was no effect of variations in serum examination time intervals on Potassium electrolyte levels, while Chloride electrolyte levels obtained a significance value of p = 0,002 meaning that there is an effect of variations in serum examination time intervals on Chloride electrolyte levels.